Smoking and maras powder use by pregnant women living in kahramanmaras and associated factors - Akyıldız, Deniz; Öztaş, Hatice Gül; Erdi, Gülnaz (Journal of Dependence, 2023)
Objective: This study aimed to determine the smoking and Maras powder use by pregnant women living in Kahramanmaras and associated factors. Method: This research, a cross-sectional study method, was carried out in a state hospital in Kahramanmaras with 669 pregnant women. Research data were collected by the face-to-face meeting method through a questionnaire form. Results: 12.9% of the pregnant women smoked cigarettes, and 4.9% used Maras powder. The probability of smoking during pregnancy was high for women who graduated from primary school (OR=1.80; 95% CI=0.57-5.72), with a low-income level (OR=7.95; 95% CI=2.91-21.68), women without health insurance (OR=0.05; 95% CI=0.01-0.30), women who lived in the city (OR=4.40; 95% CI=1.14-16.93), women who perceived the relationship with their spouse negatively (OR=7.26; 95% CI=1.24-42.33), women who were smoking before pregnancy (OR=269.61; 95% CI=202.76-351.32), and whose spouses were smoking cigarettes (OR=1.29; 95% CI=1.14-1.47) and using Maras powder (OR=0.15; 95% CI=0.04-0.54). The rate of Maras powder use during pregnancy was high for women who had a negative relationship with their spouses (OR=3.29; 95% CI=1.32-8.16), whose spouses used Maraş powder (OR=4.41; 95% CI=1.83-10.65), and who also used Maras powder during pre-pregnancy (OR=2.41; 95% CI) =0.94-6.15). Conclusion: This study determined that a considerable number of women smoked cigarettes and used Maras powder during their pregnancies. It is recommended that new studies be planned to determine the use of Maras powder during pregnancy in Kahramanmaraş and its surrounding provinces.